EFFECT EFFECT OF ADDITION OF CHITOSAN AND GLYCEROL ON BIOPLASTICS ORIGINATED FROM MELINJO SEEDS (Gnetum gnemon) - Nurraihan , Riska Putri; Kamaliah; Harahap, Diannita; Nisah, Khairun (SciencePlus, 2025)
One solution to the plastic waste problem is to produce environmentally friendly plastic made from melinjo starch (Gnetum gnemon). The objective of this research is to determine whether bioplastic made from melinjo seeds (Gnetum gnemon) can be used as a starch-based material for producing eco-friendly plastic and to assess the impact of adding chitosan and glycerol to bioplastic derived from melinjo seeds (Gnetum gnemon). The research method employed is a qualitative and quantitative descriptive analysis of the resulting bioplastic, which consists of seven stages: starch production, bioplastic production, solubility test, swelling test, water resistance test, moisture content test, and biodegradability test. The results show that the composition with 4 grams of melinjo seed starch without the addition of chitosan and glycerol has low solubility (0%) and swelling (2.63%), high water resistance (97.37%), low moisture content (1.97%), and optimal biodegradation rate (97%). The addition of chitosan and glycerol affects the properties of bioplastic derived from melinjo seeds. This addition can increase solubility (2%), reduce the swelling percentage (1.47%), increase moisture content (3.11%), enhance water resistance (98.53%), and reduce the biodegradability percentage of bioplastic (97%).